Republic of Congo : Technical Assistance Report-National Accounts Mission. (IMF Staff Country Reports; Country Report ;, 2020)
A technical assistance mission in national accounting from the International Monetary Fund (IMF) Regional Technical Assistance Center for Central Africa (AFRITAC Central) visited Brazzaville during December 5-14, 2018 to support the National Statistics Institute (INS) in its work on the national accounts estimates. The mission focused on an analysis of the 2016 and 2017 annual national accounts finalized in accordance with the System of National Accounts 1993 (1993 SNA). The analysis included a review of the information sources used, the methods of calculation and extrapolation, and compliance with the 1993 SNA. The 2016 accounts are completed and finalized, including the summary tables - supply and use tables (SUT), branch accounts, and integrated economic accounts table (IEAT); and the 2017 accounts are still being finalized. The mission recommends that the national accounting officers improve estimates based on the recommendations provided by the mission.1.